PENANGANAN HIPERTENSI PADA LANSIA DI KOMUNITAS (Pemberian Terapi Senam Erobik Low Impact, edukasi dan pemeriksaan kesehatan Pada Lansia Di Kelurahan Bujel Kota Kediri Tahun 2025) - ramayanti, eva dwi (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Elderly individuals experience a degenerative process. One of the factors contributing to the decline in body function is the neurocirculatory system. This condition leads to hypertension. Therefore, efforts are needed to address hypertension in the elderly in the community. These measures include education, health checks, and complementary therapy in the form of low-impact aerobic exercise. A community service program is needed to address hypertension in the elderly in the community. The three-day community service program consisted of health education on hypertension on the first day, health checks on the second day, and low-impact aerobic exercise therapy on the third day. The program ran smoothly, in accordance with the contract and objectives. Participants enthusiastically participated in each session until its completion. Participants reported a greater understanding of hypertension. The health check results were summarized in the community health center, and low-impact aerobic exercise was administered according to standard operating procedures (SOP). The community service program